Perancangan Sistem Pelayanan Jasa Laundry Berbasis PHP pada UMKM Laundry Lemon Fresh - Lia Apriliani; Fadzar Rusghana (Melati Institute, 2023)
Laundry Lemon Fresh is one of the MSMEs providing laundry services that still uses manual transactions by recording customer data and recording transactions manually without being computerized. The purpose of creating this system is to make it easier for customers and laundry business owners to manage customer data, transactions, and financial reports. The service system at MSME Laundry Lemon Fresh is made with the waterfall method. The application used is Visual Studio Code and with the PHP programming language. The database used is PhpmyAdmin. With this system, it is hoped that data processing can be done easily and can avoid recording errors as occurs if you record manually.